CURRENT STATUS OF WILLINGNESS TO CONSENT TO THE DONATION OF HUMAN TISSUES AND ORGANS DURING LIFE AMONG ADULTS ATTENDING COMMUNE HEALTH STATIONS IN CAM LE DISTRICT, DA NANG CITY (Vietnam Journal of Community Medicine, 2026)
Objective: To describe willingness to donate human tissues and organs while alive and to examine factors associated with this willingness among adults attending commune health stations in Cam Le district, Da Nang city.Methods: A cross-sectional study was conducted from July 2024 to June 2025 among 570 adults at six commune health stations. Data were collected using a structured KAP questionnaire. The knowledge section included 13 items and the attitude section included 9 items; scores of at least 75% were classified as adequate. The dependent variable was willingness to donate while alive (yes/no). Descriptive statistics, Chi-square tests, univariable logistic regression, and multivariable logistic regression with robust standard errors were used to estimate crude and adjusted odds ratios with 95% confidence intervals.Results: The proportion of participants willing to donate human tissues and organs while alive was 31.1%. Common reasons for hesitation included concerns about health safety (26.1%), impact on family (20.5%), lack of family agreement (17.8%), fear and anxiety (15.5%), and fear of social judgment (14.2%). In the multivariable model, adults aged 35–44, 45–60, and >60 years had lower odds of willingness than those aged 18–24 years, whereas having a religion and having a positive attitude were independently associated with higher odds of willingness.Conclusion: Willingness to donate human tissues and organs while living remained low. After multivariable adjustment, age group, religion, and attitude were independently associated with willingness to donate while alive.
Keywords: living donation; human tissue and organ donation; willingness; KAP; commune health station; Da Nang.